Learn with, through and {\ "about the WWW - Keil, Reinhard; Selke, Harald

Virtual knowledge {\ "a} ume - From the presentation of content to virtual learning ä tten - Keil, Reinhard; Selke, Harald

Development of a structured process of interaction design for {\ "u} r nat ü local user interfaces - Klompmaker, Florian

Empirical validation of design patterns - Schild, Christian; Petrausch, Vanessa (Human and Computer 2015 - Proceedings)
Patterns serve to codify design knowledge. By embedding them in a hypothesis-driven design, it is possible to develop them further into sample languages. For this it is necessary to resolve the underlying conflicts in the form of design hypotheses and to validate them empirically in order to enable further use and generalization. In this article, an experiment is presented that describes this procedure and demonstrates the interplay between theory formation and codification of design knowledge using two examples.

Online Resource Leasing - Markarian, Christine; Meyer auf der Heide, Friedhelm (Proceedings of the 2015 ACM Symposium on Principles of Distributed Computing (PODC))
Many markets have seen a shift from the idea of buying and moved to leasing instead. Arguably, the latter has been the major catalyst for their success. Ten years ago, research realized this shift and initiated the study of "online leasing problems" by introducing leasing to online optimization problems. Resources required to provide a service in an "online leasing problem" are no more bought but leased for different durations. In this paper, we provide an overview of results that contribute to the understanding of "online resource leasing problems".

Einstellungen von Grundschullehrkräften zum inklusiven Lernen in Abhängigkeit von dem Umfang an Erfahrungen aus dem Unterricht mit Kindern mit unterschiedlichen sonderpädagogischen Förderbedarfen - Hellmich, Frank; Görel, Gamze (Veränderung und Beständigkeit in Zeiten der Inklusion. Perspektiven sonderpädagogischer Professionalisierung)

Online Resource Leasing - Markarian, Christine

Entwicklung naturwissenschaftlich-technischer Lehr-Lernangebote für inklusiven Sachunterricht - Blumberg, Eva; Hellmich, Frank; Fromme, Theresa (Lernprozessbegleitung und adaptives Lernen in der Grundschule. Forschungsbezogene Beiträge)

Kausalattributionen von Leseerfolgen und Lesemisserfolgen bei Kindern im Leseunterricht der Grundschule - Ort, Margarita; Hellmich, Frank (Facetten grundschulpädagogischer und -didaktischer Forschung)

Lesestrategien und Leseerfolg bei Kindern im vierten Grundschuljahr – Analysen mit Fragebogen- und Beobachtungsverfahren - Hellmich, Frank (Innovative Erhebungsmethoden – dargestellt an verschiedenen Forschungsprojekten)

Online Bewertungssysteme – Ein systematischer Überblick - Lange, Alexander

Gesellschaftliche und kulturelle Bedeutung von Mittagsverpflegung in Gießener Kindertagesstätten - Klünder, Nina (Hauswirtschaft und Wissenschaft)

Verpflegung in Kindertagesstätten gestalten – Ergebnisse einer qualitativen Studie - Meier-Gräwe, Uta; Klünder, Nina (KiTa aktuell)

On-The-Fly Verification of Reconfigurable Image Processing Modules based on a Proof-Carrying Hardware Approach - Wiersema, Tobias; Wu, Sen; Platzner, Marco (Proceedings of the International Symposium in Reconfigurable Computing (ARC))
Proof-carrying hardware is an approach that has recently been proposed for the efficient verification of reconfigurable modules. We present an application of proof-carrying hardware to guarantee the correct functionality of dynamically reconfigured image processing modules. Our prototype comprises a reconfigurable-system-on-chip with an embedded virtual FPGA fabric. This setup allows us to leverage open source FPGA synthesis and backend tools to produce FPGA configuration bitstreams with an open format and, thus, to demonstrate and experimentally evaluate proof-carrying hardware at the bitstream level.

Effects of human milk and formula on postprandial glycaemia and insulinaemia - Wright, C J; Atkinson, F S; Ramalingam, N; Buyken, Anette; Brand-Miller, J C (European Journal of Clinical Nutrition)

Dietary micronutrient intake during pregnancy is a function of carbohydrate quality - Goletzke, Janina; Buyken, Anette; Louie, Jimmy CY; Moses, Robert G; Brand-Miller, Jennie C (The American Journal of Clinical Nutrition)

Early Diet and Later Cancer Risk: Prospective Associations of Dietary Patterns During Critical Periods of Childhood with the GH-IGF Axis, Insulin Resistance and Body Fatness in Younger Adulthood - Günther, Anke L. B.; Schulze, Matthias B.; Kroke, Anja; Diethelm, Katharina; Joslowski, Gesa; Krupp, Danika; Wudy, Stefan; Buyken, Anette (Nutrition and Cancer)

Relevance of fruits, vegetables and flavonoids from fruits and vegetables during early life, mid-childhood and adolescence for levels of insulin-like growth factor (IGF-1) and its binding proteins IGFBP-2 and IGFBP-3 in young adulthood - Krupp, Danika; Remer, Thomas; Penczynski, Katharina J.; Bolzenius, Katja; Wudy, Stefan A.; Buyken, Anette (British Journal of Nutrition)
Abstract The growth hormone (GH) insulin-like growth factor (IGF) axis has been linked to insulin metabolism and cancer risk. Experimental evidence indicates that the GH–IGF axis itself can be influenced by dietary flavonoids. As fruit and vegetable (FV) intake is a major source of flavonoid consumption, FV’s beneficial health effects may be explained via flavonoids’ influence on the GH–IGF axis, but observational evidence is currently rare. We used data from Dortmund Nutritional and Anthropometric Longitudinally Designed Study participants to analyse prospective associations between FV, fruit intake and flavonoid intake from FV (FlavFV) with IGF-1 and its binding proteins IGFBP-2 and IGFBP-3. Subjects needed to provide a fasting blood sample in adulthood (18–39 years) and at least two 3-d weighed dietary records in early life (0·5−2 years, n 191), mid-childhood (3−7 years, n 265) or adolescence (girls: 9−15 years, boys: 10−16 years, n 261). Additional analyses were conducted among those providing at least three 24-h urine samples in adolescence ( n 236) to address the predictor urinary hippuric acid (HA), a biomarker of polyphenol intake. Higher fruit intake in mid-childhood and adolescence was related to higher IGFBP-2 in adulthood ( P =0·03 and P =0·045). Comparable trends ( P =0·045−0·09) were discernable for FV intake (but not FlavFV) in all three time windows. Similarly, higher adolescent HA excretion tended to be related ( P =0·06) to higher adult IGFBP-2 levels. Regarding IGFBP-3, a marginal ( P =0·08) positive association was observed with FlavFV in mid-childhood only. None of the investigated dietary factors was related to IGF-1. In conclusion, higher fruit and FV intakes during growth may be relevant for adult IGFBP-2, but probably not for IGFBP-3 or IGF-1.

Relative validation of 24-h urinary hippuric acid excretion as a biomarker for dietary flavonoid intake from fruit and vegetables in healthy adolescents - Penczynski, Katharina J.; Krupp, Danika; Bring, Anna; Bolzenius, Katja; Remer, Thomas; Buyken, Anette (European Journal of Nutrition)

Approximate Pure Nash Equilibria in Weighted Congestion Games: Existence, Efficient Computation, and Structure - Caragiannis, Ioannis; Fanelli, Angelo; Gravin, Nick; Skopalik, Alexander (Transactions on Economics and Computation)
We consider structural and algorithmic questions related to the Nash dynamics of weighted congestion games. In weighted congestion games with linear latency functions, the existence of pure Nash equilibria is guaranteed by a potential function argument. Unfortunately, this proof of existence is inefficient and computing pure Nash equilibria in such games is a PLS-hard problem even when all players have unit weights. The situation gets worse when superlinear (e.g., quadratic) latency functions come into play; in this case, the Nash dynamics of the game may contain cycles and pure Nash equilibria may not even exist. Given these obstacles, we consider approximate pure Nash equilibria as alternative solution concepts. A ρ--approximate pure Nash equilibrium is a state of a (weighted congestion) game from which no player has any incentive to deviate in order to improve her cost by a multiplicative factor higher than ρ. Do such equilibria exist for small values of ρ? And if so, can we compute them efficiently?We provide positive answers to both questions for weighted congestion games with polynomial latency functions by exploiting an “approximation” of such games by a new class of potential games that we call Ψ-games. This allows us to show that these games have d!-approximate pure Nash equilibria, where d is the maximum degree of the latency functions. Our main technical contribution is an efficient algorithm for computing O(1)-approximate pure Nash equilibria when d is a constant. For games with linear latency functions, the approximation guarantee is 3+√5/2 + Oγ for arbitrarily small γ > 0; for latency functions with maximum degree d≥ 2, it is d2d+o(d). The running time is polynomial in the number of bits in the representation of the game and 1/γ. As a byproduct of our techniques, we also show the following interesting structural statement for weighted congestion games with polynomial latency functions of maximum degree d ≥ 2: polynomially-long sequences of best-response moves from any initial state to a dO(d2)-approximate pure Nash equilibrium exist and can be efficiently identified in such games as long as d is a constant.To the best of our knowledge, these are the first positive algorithmic results for approximate pure Nash equilibria in weighted congestion games. Our techniques significantly extend our recent work on unweighted congestion games through the use of Ψ-games. The concept of approximating nonpotential games by potential ones is interesting in itself and might have further applications.

Anonymous credential system based on q-Strong Diffie-Hellman Assumption - Eidens, Fabian

Anonymous and Publicly Linkable Reputation Systems - Blömer, Johannes; Juhnke, Jakob; Kolb, Christina (Proceedings of the 18th International Conference on Financial Cryptography and Data Security (FC))
Reputation systems are used to compute and publish reputation scores for services or products. We consider reputation systems where users are allowed to rate products that they purchased previously. To obtain trustworthy reputations, they are allowed to rate these products only once. As long as users rate products once, they stay anonymous. Everybody is able to detect users deviating from the rate-products-only-once policy and the anonymity of such dishonest users can be revoked by a system manager. In this paper we present formal models for such reputation systems and their security. Based on group signatures presented by Boneh, Boyen, and Shacham we design an efficient reputation system that meets all our requirements.

An approach towards adaptive service composition in markets of composed services - Jungmann, Alexander; Mohr, Felix (Journal of Internet Services and Applications)
On-the-fly composition of service-based software solutions is still a challenging task. Even more challenges emerge when facing automatic service composition in markets of composed services for end users. In this paper, we focus on the functional discrepancy between “what a user wants” specified in terms of a request and “what a user gets” when executing a composed service. To meet the challenge of functional discrepancy, we propose the combination of existing symbolic composition approaches with machine learning techniques. We developed a learning recommendation system that expands the capabilities of existing composition algorithms to facilitate adaptivity and consequently reduces functional discrepancy. As a representative of symbolic techniques, an Artificial Intelligence planning based approach produces solutions that are correct with respect to formal specifications. Our learning recommendation system supports the symbolic approach in decision-making. Reinforcement Learning techniques enable the recommendation system to adjust its recommendation strategy over time based on user ratings. We implemented the proposed functionality in terms of a prototypical composition framework. Preliminary results from experiments conducted in the image processing domain illustrate the benefit of combining both complementary techniques.

A Metric for Functional Reusability of Services - Mohr, Felix (Proceedings of the 14th International Conference on Software Reuse (ICSR))
Services are self-contained software components that can beused platform independent and that aim at maximizing software reuse. Abasic concern in service oriented architectures is to measure the reusabilityof services. One of the most important qualities is the functionalreusability, which indicates how relevant the task is that a service solves.Current metrics for functional reusability of software, however, have verylittle explanatory power and do not accomplish this goal.This paper presents a new approach to estimate the functional reusabilityof services based on their relevance. To this end, it denes the degreeto which a service enables the execution of other services as its contri-bution. Based on the contribution, relevance of services is dened as anestimation for their functional reusability. Explanatory power is obtainedby normalizing relevance values with a reference service. The applicationof the metric to a service test set conrms its supposed capabilities.

A Group Signature Scheme with Distributed Group Management - An Application of Threshold Encryption - Löken, Nils

A group signature scheme based on the LSRW assumption - Heihoff, Frederic

A deterministic worst-case message complexity optimal solution for resource discovery - Kniesburges, Sebastian; Koutsopoulos, Andreas; Scheideler, Christian (Theoretical Computer Science)
We consider the problem of resource discovery in distributed systems. In particular we give an algorithm, such that each node in a network discovers the address of any other node in the network. We model the knowledge of the nodes as a virtual overlay network given by a directed graph such that complete knowledge of all nodes corresponds to a complete graph in the overlay network. Although there are several solutions for resource discovery, our solution is the first that achieves worst-case optimal work for each node, i.e. the number of addresses (O(n)O(n)) or bits (O(nlog⁡n)O(nlog⁡n)) a node receives or sends coincides with the lower bound, while ensuring only a linear runtime (O(n)O(n)) on the number of rounds.

Will They Die Another Day? A Decision Support Perspective on Reusing Electric Vehicle Batteries - Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

A Market for Trading Used Electric Vehicle Batteries — Theoretical Foundations and Information Systems - Klör, Benjamin; Beverungen, Daniel; Bräuer, Sebastian; Plenter, Florian; Monhof, Markus (Proceedings of the Twenty-Third European Conference on Information Systems (ECIS 2015))

Sustaining Civil Peace: a configurational comparative analysis - Gries, Thomas; Palnau, Irene (Peace Economics, Peace Science and Public Policy)

Oppressive Governments, Dependence on the United States and Anti-American Terrorism - Gries, Thomas; Meierrieks, Daniel; Redlin, Margarete (Oxford Economic Papers)

Erfolg durch Persönlichkeit? Der Einfluss der Markenpersönlichkeit auf den Zusammenhang von Reputation und Unternehmenserfolg - Fanasch, Patrizia

Die Veränderung des Mobilfunkmarktes durch die Discountanbieter - Walczok, Gregor Paul

Learning Boolean Specifications - Bubeck, Uwe; Kleine Büning, Hans (Artificial Intelligence)
In this paper we consider an extended variant of query learning where the hidden concept is embedded in some Boolean circuit. This additional processing layer modifies query arguments and answers by fixed transformation functions which are known to the learner. For this scenario, we provide a characterization of the solution space and an ordering on it. We give a compact representation of the minimal and maximal solutions as quantified Boolean formulas and we adapt the original algorithms for exact learning of specific classes of propositional formulas.
Keywords: Query learning; Propositional logic

Evaluation von Bildverarbeitungsalgorithmen in heterogenen Rechenknoten - Knorr, Christoph

A Domain-Specific Modeling Language for Electric Vehicle Batteries - Klör, Benjamin; Bräuer, Sebastian; Beverungen, Daniel; Monhof, Markus (Proceedings of the 12. International Conference on Wirtschaftsinformatik 2015 (WI 2015))

Extending Battery Management Systems for Making Informed Decisions on Battery Reuse - Monhof, Markus; Beverungen, Daniel; Klör, Benjamin; Bräuer, Sebastian (New Horizons in Design Science: Broadening the Research Agenda)

Neue Bildungslandschaften - Kommunales Bildungsmanagement als Zukunftsaufgabe - Euler, Dieter; Sloane, Peter F. E. (Zeitschrift für Berufs-und Wirtschaftspädagogik)

Die Bedeutung subjektiver Sichtweisen für die Implementierung betrieblicher Lernkultur - Fischer, Christoph; Harteis, Christian (Informelles Lernen, Annäherungen - Problemlagen - Forschungsbefunde)
Keywords: Epistemische Überzeugungen; learning culture

Effects of age, gender and occupation on perceived workplace learning support - Harteis, Christian; Billett, Stephen; Goller, Michael; Rausch, Andreas; Seifried, J{\ (International journal of training research)

Bedingungsfaktoren beruflichen Könnens - Harteis, Christian (Konzepte und Ergebnisse ausgewählter Forschungsfelder der beruflichen Bildung)

A Shared Task on Argumentation Mining in Newspaper Editorials - Kiesel, Johannes; Al-Khatib, Khalid; Hagen, Matthias; Stein, Benno (Proceedings of the 2nd Workshop on Argumentation Mining)

A Shared Task on Argumentation Mining in Newspaper Editorials - Kiesel, Johannes; Al-Khatib, Khalid; Hagen, Matthias; Stein, Benno (Proceedings of the 2nd Workshop on Argumentation Mining)

Sentiment Flow - A General Model of Web Review Argumentation - Wachsmuth, Henning; Kiesel, Johannes; Stein, Benno (Proceedings of the 2015 Conference on Empirical Methods in Natural Language Processing)

Planar prism spectrometer based on adiabatically connected waveguiding slabs - Civitci, F.; Hammer, Manfred; Hoekstra, H.J.W.M. (Optics Communications)
The device principle of a prism-based on-chip spectrometer for TE polarization is introduced. The spectrometer exploits the modal dispersion in planar waveguides in a layout with slab regions having two different thicknesses of the guiding layer. The set-up uses parabolic mirrors, for the collimation of light of the input waveguide and focusing of the light to the receiver waveguides, which relies on total internal reflection at the interface between two such regions. These regions are connected adiabatically to prevent unwanted mode conversion and loss at the edges of the prism. The structure can be fabricated with two wet etching steps. The paper presents basic theory and a general approach for device optimization. The latter is illustrated with a numerical example assuming SiON technology.
Keywords: tet_topic_waveguide

Full Resonant Transmission of Semiguided Planar Waves Through Slab Waveguide Steps at Oblique Incidence - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Journal of Lightwave Technology)
Sheets of slab waveguides with sharp corners are investigated. By means of rigorous numerical experiments, we look at oblique incidence of semi-guided plane waves. Radiation losses vanish beyond a certain critical angle of incidence. One can thus realize lossless propagation through 90-degree corner configurations, where the remaining guided waves are still subject to pronounced reflection and polarization conversion. A system of two corners can be viewed as a structure akin to a Fabry-Perot-interferometer. By adjusting the distance between the two partial reflectors, here the 90-degree corners, one identifies step-like configurations that transmit the semi-guided plane waves without radiation losses, and virtually without reflections. Simulations of semi-guided beams with in-plane wide Gaussian profiles show that the effect survives in a true 3-D framework.
Keywords: tet_topic_waveguide

Text Analysis Pipelines - Towards Ad-hoc Large-scale Text Mining - Wachsmuth, Henning

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

How planar optical waves can be made to climb dielectric steps - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Optics Letters)
We show how to optically connect guiding layers at different elevations in a 3-D integrated photonic circuit. Transfer of optical power carried by planar, semi-guided waves is possible without reflections or radiation losses, and over large vertical distances. This functionality is realized through simple step-like folds of high-contrast dielectric slab waveguides, in combination with oblique wave incidence, and fulfilling a resonance condition. Radiation losses vanish, and polarization conversion is suppressed for TE wave incidence beyond certain critical angles. This can be understood by fundamental arguments resting on a version of Snell’s law. The two 90° corners of a step act as identical partial reflectors in a Fabry–Perot-like resonator setup. By selecting the step height, i.e., the distance between the reflectors, one realizes resonant states with full transmission. Rigorous quasi-analytical simulations for typical silicon/silica parameters demonstrate the functioning. Combinations of several step junctions can lead to other types of optical on-chip connects, e.g., U-turn- or bridge-like configurations.
Keywords: tet_topic_waveguide

Subwavelength binary plasmonic solitons - Kou, Yao; Förstner, Jens (Optics Letters)
We study the formation of subwavelength solitons in binary metal-dielectric lattices. We show that the transverse modulation of the lattice constant breaks the fundamental plasmonic band and suppresses the discrete diffraction of surface plasmon waves. New types of plasmonic solitons are found, and their characteristics are analyzed. We also demonstrate the existence of photonic-plasmonic vector solitons and elucidate their propagation properties.
Keywords: tet_topic_polariton

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

How do reviews from professional critics interact with other signals of product quality? Evidence from the video game industry - Cox, Joe; Kaimann, Daniel (Journal of Consumer Behaviour)
Experience goods are characterised by information asymmetry and a lack of ex ante knowledge of product quality, such that reliable external signals of quality are likely to be highly valued. Two potentially credible sources of such information are reviews from professional critics and ‘word of mouth’ from other consumers. This paper makes a direct comparison between the relative influences and interactions of reviews from both of these sources on the sales performance of video game software. In order to empirically estimate and separate the effects of the two signals, we analyze a sample of 1480 video games and their sales figures between 2004 and 2010. We find evidence to suggest that even after taking steps to control for endogeneity, reviews from professional critics have a significantly positive influence on sales which outweighs that from consumer reviews. We also find evidence to suggest that reviews from professional critics also interact significantly with other signals of product quality. Consequently, we contend that professional critics adopt the role of an influencer, whereas word-of-mouth opinion acts more as a predictor of sales in the market for video games.

How do Different Sources of the Variance of Consumer Ratings Matter? - Herrmann, Philipp; Kundisch, Dennis; Zimmermann, Steffen; Nault, Barry (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth)
We examine the effect of the variance of consumer ratings on product pricing and sales using an analytical model, which considers goods that are characterized by experience attributes and informed search attributes (i.e., experience attributes that were transformed in search attributes by consumer ratings). For pure informed search goods, equilibrium price increases and demand decreases in variance. For pure experience goods, equilibrium price and demand decrease in variance. For hybrid goods with low total variance, equilibrium price and demand increase with an increasing relative share of variance caused by informed search attributes when the average rating and total variance of ratings are held constant. Hence, risk-averse consumers may prefer a more expensive good with a higher variance of ratings out of two similar goods with the same average rating. Moreover, our analytical model provides a theoretical foundation for the empirically observed j-shaped distribution of consumer ratings in electronic commerce.

Grammar-based model transformations: Definition, execution, and quality properties - Besova, Galina; Steenken, Dominik; Wehrheim, Heike (Computer Languages, Systems & Structures)
Model transformation is a key concept in model-driven software engineering. The definition of model transformations is usually based on meta-models describing the abstract syntax of languages. While meta-models are thereby able to abstract from uperfluous details of concrete syntax, they often loose structural information inherent in languages, like information on model elements always occurring together in particular shapes. As a consequence, model transformations cannot naturally re-use language structures, thus leading to unnecessary complexity in their development as well as in quality assurance.In this paper, we propose a new approach to model transformation development which allows to simplify the developed transformations and improve their quality via the exploitation of the languages׳ structures. The approach is based on context-free graph grammars and transformations defined by pairing productions of source and target grammars. We show that such transformations have important properties: they terminate and are sound, complete, and deterministic.

Fuzzy Matching von Vor- und Nachbedingungen in Servicespezikationen - Börding, Paul

Fusionen von gesetzlichen Krankenversicherungen zu den Effizienz- und Wechselwirkungen - Osburg, Christina

Tightly-Secure Signatures from Chameleon Hash Functions - Blazy, Olivier; Kakvi, Saqib; Kiltz, Eike; Pan, Jiaxin (Lecture Notes in Computer Science)

Filtering Reviews by Random Individual Error - Geierhos, Michaela; Bäumer, Frederik Simon; Schulze, Sabine; Stuß, Valentina (Proceedings of the 28th International Conference on Industrial, Engineering and Other Applications of Applied Intelligent Systems (IEA/AIE 2015))
Opinion mining from physician rating websites depends on the quality of the extracted information. Sometimes reviews are user-error prone and the assigned stars or grades contradict the associated content. We therefore aim at detecting random individual error within reviews. Such errors comprise the disagreement in polarity of review texts and the respective ratings. The challenges that thereby arise are (1) the content and sentiment analysis of the review texts and (2) the removal of the random individual errors contained therein. To solve these tasks, we assign polarities to automatically recognized opinion phrases in reviews and then check for divergence in rating and text polarity. The novelty of our approach is that we improve user-generated data quality by excluding error-prone reviews on German physician websites from average ratings.

Fair Trade - Eine neue Perspektive in der internationalen Handelspolitik - Materna, GinaJoanna

Fair Trade - An economic investigation of benefits and drawbacks - Goronczewski, Patricia

Evaluation of Pairing Optimization for Embedded Platforms - Sosniak, Martin

Entwicklung von Ablösesummen und Gehälter in der Fußball-Bundesliga - Salary Caps als mögliches Modell der Chancengleichheit - Plonka, Dennis

Elektromagnetische Seitenkanalangriffe auf paarungsbasierte Kryptographie - Gerken, Britta

Ausgewählte Probleme des Logistikmanagements

Ein Framework für Fuzzy Service Matching basierend auf Fuzzy Sets - Neumann, Conrad

Efficient Verifier-Local Revocation for Anonymous Credentials - Bobolz, Jan

Efficient Attributes for Pairing-Based Anonymous Credentials - Stroh, Christian

Dynamics and Efficiency in Topological Self-Stabilization - Koutsopoulos, Andreas

Distributed Data Structures and the Power of topological Self-Stabilization - Kniesburges, Sebastian

Diffusion of Innovations in Social Networks - Kunisch, Christina

Die Wirksamkeit von Zertifikaten als Qualitätssignal - Reimann, Alina

Die Einführung der EU-Merger Guidelines - Effizienz und Wohlfahrtswirkungen - Topal, Barlas

Design of an Evaluation Strategy for Fuzzy Service Matching - Bruns, Melanie

Constructions of Fully Secure Predicate Encryption Schemes - Schleiter, Patrick

Confined Guessing: New Signatures From Standard Assumptions - Böhl, Florian; Hofheinz, Dennis; Jager, Tibor; Koch, Jessica; Striecks, Christoph (J. Cryptology)

On the Security of TLS 1.3 and QUIC Against Weaknesses in PKCS#1 v1.5 Encryption - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Proceedings of the 22nd ACM SIGSAC Conference on Computer and Communications Security, Denver, CO, USA, October 12-16, 2015)

Practical Invalid Curve Attacks on TLS-ECDH - Jager, Tibor; Schwenk, Jörg; Somorovsky, Juraj (Computer Security - ESORICS 2015 - 20th European Symposium on Research in Computer Security, Vienna, Austria, September 21-25, 2015, Proceedings, Part I)

On the Selective Opening Security of Practical Public-Key Encryption Schemes - Heuer, Felix; Jager, Tibor; Kiltz, Eike; Schäge, Sven (Public-Key Cryptography - PKC 2015 - 18th IACR International Conference on Practice and Theory in Public-Key Cryptography, Gaithersburg, MD, USA, March 30 - April 1, 2015, Proceedings)

One-Round Key Exchange with Strong Security: An Efficient and Generic Construction in the Standard Model - Bergsma, Florian; Jager, Tibor; Schwenk, Jörg (Public-Key Cryptography - PKC 2015 - 18th IACR International Conference on Practice and Theory in Public-Key Cryptography, Gaithersburg, MD, USA, March 30 - April 1, 2015, Proceedings)

Verifiable Random Functions from Weaker Assumptions - Jager, Tibor (Theory of Cryptography - 12th Theory of Cryptography Conference, TCC 2015, Warsaw, Poland, March 23-25, 2015, Proceedings, Part II)

Tightly-Secure Authenticated Key Exchange - Bader, Christoph; Hofheinz, Dennis; Jager, Tibor; Kiltz, Eike; Li, Yong (Theory of Cryptography - 12th Theory of Cryptography Conference, TCC 2015, Warsaw, Poland, March 23-25, 2015, Proceedings, Part I)

Comprehensive Service Matching with MatchBox - Börding, Paul; Bruns, Melanie; Platenius, Marie Christin (10th Joint Meeting of the European Software Engineering Conference and the ACM SIGSOFT Symposium on the Foundations of Software Engineering (ESEC/FSE'15))
Nowadays, many service providers offer software components in the form of Software as a Service. Requesters that want to discover those services in order to use or to integrate them, need to find out which service satisfies their requirements best. For this purpose, service matching approaches determine how well the specifications of provided services satisfy their requirements (including structural, behavioral, and non-functional requirements). In this paper, we describe the tool-suite MatchBox that allows the integration of existing service matchers and their combination as part of flexibly configurable matching processes. Taking requirements and service specifications as an input, MatchBox is able to execute such matching processes and deliver rich matching results. In contrast to related tools, MatchBox allows users to take into account many different kinds of requirements, while it also provides the flexibility to control the matching process in many different ways.

Competition and Product Innovation of Intermediaries in a Differentiated Duopoly - Brangewitz, Sonja; Manegold, Jochen
On an intermediate goods market we allow for vertical and horizontal product differentiation and analyze the influence of simultaneous competition for resources and customers on the market outcome. Asymmetries between intermediaries cannot arise just from distinct product qualities, but also from different production technologies. The intermediaries face either price or quantity competition on the output market and a monopolistic input supplier on the input market. We find that there exist quality and productivity differences such that for quantity competition only one intermediary is willing to procure inputs from the input supplier, while for price competition both intermediaries are willing to purchase inputs. Considering product innovation for symmetric productivities we derive equilibrium conditions on the investment costs and compare price and quantity competition. It turns out that on the one hand there exist product qualities and degrees of horizontal product differentiation for complements such that asymmetric investment equilibria fail to exist. On the other hand we find that there also exist product qualities and degrees of horizontal product differentiation for substitutes such that existence can be guaranteed if the investment costs are chosen accordingly.

Combining Service-oriented Computing with Embedded Systems - A Robotics Case Study - Jungmann, Alexander; Jatzkowski, Jan; Kleinjohann, Bernd (Proceedings of the 5th IFIP International Embedded Systems Symposium)
In this paper, we introduce an approach for combining embedded systems with Service-oriented Computing techniques based on a concrete application scenario from the robotics domain. Our proposed Service-oriented Architecture allows for incorporating computational expensive functionality as services into a distributed computing environment. Furthermore, our framework facilitates a seamless integration of embedded systems such as robots as service providers into the computing environment. The entire communication is based on so-called recipes, which can be interpreted as autonomous messages that contain all necessary information for executing compositions of services.

Budget Games with priced strategies - Pautz, Jannis

Temporal plans for software architecture reconfiguration - Ziegert, Steffen; Wehrheim, Heike (Computer Science - R & D)

From Program Verification to Time and Space: The Scientific Life of Ernst-Rüdiger Olderog - Meyer, Roland; Wehrheim, Heike (Correct System Design - Symposium in Honor of Ernst-Rüdiger Olderog on the Occasion of His 60th Birthday, Oldenburg, Germany, September 8-9, 2015. Proceedings)

Verifying Opacity of a Transactional Mutex Lock - Derrick, John; Dongol, Brijesh; Schellhorn, Gerhard; Travkin, Oleg; Wehrheim, Heike (FM 2015: Formal Methods - 20th International Symposium, Oslo, Norway, June 24-26, 2015, Proceedings)

TSO to SC via Symbolic Execution - Wehrheim, Heike; Travkin, Oleg (Hardware and Software: Verification and Testing - 11th International Haifa Verification Conference, HVC 2015, Haifa, Israel, November 17-19, 2015, Proceedings)

Correct System Design - Symposium in Honor of Ernst-Rüdiger Olderog on the Occasion of His 60th Birthday, Oldenburg, Germany, September 8-9, 2015. Proceedings

Bewertung von Renderingalgorithmen für komplexe 3-D-Szenen - Jähn, Claudius

Automatic Service Discovery and Composition for heterogeneous service partners - Huma, Zille

Automated Online Service Composition - Mohr, Felix; Jungmann, Alexander; Kleine Büning, Hans (Proceedings of the 12th IEEE International Conference on Services Computing (SCC))
Services are self-contained and platform independent software components that aim at maximizing software reuse. The automated composition of services to a target software artifact has been tackled with many AI techniques, but existing approaches make unreasonably strong assumptions such as a predefined data flow, are limited to tiny problem sizes, ignore non-functional properties, or assume offline service repositories. This paper presents an algorithm that automatically composes services without making such assumptions. We employ a backward search algorithm that starts from an empty composition and prepends service calls to already discovered candidates until a solution is found. Available services are determined during the search process. We implemented our algorithm, performed an experimental evaluation, and compared it to other approaches.

On the Complexity of Fundamental Problems in Dynamic Ad-hoc Networks - Abshoff, Sebastian

Glycemic index, glycemic load and glycemic response: An International Scientific Consensus Summit from the International Carbohydrate Quality Consortium (ICQC) - Augustin, L.S.A.; Kendall, C.W.C.; Jenkins, D.J.A.; Willett, W.C.; Astrup, A.; Barclay, A.W.; Björck, I.; Brand-Miller, J.C.; Brighenti, F.; Buyken, Anette; Ceriello, A.; La Vecchia, C.; et al. (Nutrition, Metabolism and Cardiovascular Diseases)

DUC - Fostering Diversity Aspects in Higher Education by eLearning and User generated Content - Beutner, Marc; Kundisch, Dennis; Magenheim, J.; Rechuel, R. (Proceedings of E-LEARN 2015 - World Conference on E-Learning)

Behavioral Mechanisms Prompted by Virtual Rewards: The Small-Area Hypothesis - Mutter, Tobias; Kundisch, Dennis (Proceedings of the 23rd European Conference on Information Systems (ECIS))

Fatty acid supply with complementary foods and LC-PUFA status in healthy infants: results of a randomised controlled trial - Libuda, Lars; Mesch, Christina M.; Stimming, Madlen; Demmelmair, Hans; Koletzko, Berthold; Warschburger, Petra; Blanke, Katharina; Reischl, Eva; Kalhoff, Hermann; Kersting, Mathilde (European Journal of Nutrition)

Short-term effects of lunch on children's executive cognitive functioning: The randomized crossover Cognition Intervention Study Dortmund PLUS (CogniDo PLUS) - Schröder, Maike; Müller, Katrin; Falkenstein, Michael; Stehle, Peter; Kersting, Mathilde; Libuda, Lars (Physiology & Behavior)

Interactions in IS Project Portfolio Selection: Status Quo and Perspective - Müller, M.; Meier, Christian; Kundisch, Dennis; Zimmermann, Steffen (Wirtschaftsinformatik Proceedings)